Vilnius Alma Mater – Cultural and Scientific Link of Polish-Lithuanian History - Misiak, Małgorzata (Slavistica Vilnensis, 2021)
The discussed monograph is an attempt to present Vilnius Alma Mater as a cultural and scientific link of Polish-Lithuanian history. The texts that make up the volume concern thematically Polish-Lithuanian relations from the 16th century to the present day, perceived in several aspects: historical and cultural, literary, linguistic and educational. The articles collected in the volume are arranged into specific five themes. These are: the heritage of the Polish–Lithuanian Commonwealth, the Grand Duchy of Lithuania in the works of 19th-century artists, The History of Stefan Batory University (1919–1939), The interpretation of the space of Vilnius and the Grand Duchy of Lithuania from the perspective of the 20th and 21st centuries, the study of phenomena belonging to the cultural and cultural borderland linguistic.